A comprehensive review on the potential effect of silicon fertilizer and its significance for agriculture - Abdul Munir, Fatin Diana; Sulaiman, Zulkefly; Ahmad, Khairulmazmi; Abd Samad, Mohd Yusoff; Ariffin, Mohd Rizal; Salisu, Monsuru Adekunle (USBD TECH, 2023)
Silicon (Si) is one of the most prevalent elements in the Plant’s crust which is mostly made up of silicates. Si is not regarded as needed for plant growth and development; nonetheless, there is growing evidence in the literature that this metalloid is advantageous to plants, particularly when plants are under stress. Silicon (Si) is notoriously difficult to eradicate from the nutritional substrate of plants, it has been impossible to demonstrate that plants cannot finish their life cycles without Silicon. Nevertheless, plants get advantages from the presence of Silicon, and it has been shown that Si may boost the plant's resistance to both biotic and abiotic challenges, providing the plant with protection and stability. By analyzing the data that is currently accessible in the published research, this investigation will explore the positive impact of silicon on plant growth. Si transporters are responsible for mediating the movement of Silicon, which is taken up in silicic acid. The amorphous SiO2 structures known as phytolites are generated inside the plant. The decomposition of plants results in the return of phytolites to the soil, which in turn results in the return of Silicon to the soil, where subsequent generations of plants can take it up. Many other kinds of proteins work in concert with Si to protect plants from various pathogens. These data indicate that Silicon must be classified as a necessary plant nutrient rather than just a helpful one. In this study, we highlight the function of Silicon in the soil as well as in plants, particularly with a focus on micronutrients, metabolites, Si fertilizer, crop quality, Prophylactic effects from crop diseases, phytolites, and their importance, the role of Silicon in plant roots, the role of Silicon in plant protection, stabilization, and enhancing plant health and performances, and the role of Silicon in phytolites.